1986
DOI: 10.1111/j.1432-1033.1986.tb09439.x
|View full text |Cite
|
Sign up to set email alerts
|

Structural, immunological and kinetic comparisons of NADP‐dependent malate dehydrogenases from spinach (C3) and corn (C4) chloroplasts

Abstract: This paper compares structural, immunological and kinetic properties of corn (C,) and spinach (C,) NADPmalate dehydrogenases. These chloroplastic enzymes are regulated in vivo by thiol -disulfide interchange. Both in their oxidized (inactive) and reduced (active) states these enzymes have a dimeric structure with molecular masses for the subunit ranging from 28 kDa to 38 kDa according to the procedure used for the determination. These enzymes are thus structurally related. The use of specific antibodies showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In land plants, the activity of NADP-MDH is strictly controlled by reversible reduction of the two redox active disulfide bridges through the Fdx/Trx system. C4 plants which trap CO 2 as malate contain a significantly higher level of NADP-MDH than their C3 counterparts (71). Although its mechanism of redox regulation is rather complex, NADP-MDH is the best understood of the light-activated enzymes of chloroplasts.…”
Section: Nadp-dependent Malate Dehydrogenasementioning
confidence: 99%
“…In land plants, the activity of NADP-MDH is strictly controlled by reversible reduction of the two redox active disulfide bridges through the Fdx/Trx system. C4 plants which trap CO 2 as malate contain a significantly higher level of NADP-MDH than their C3 counterparts (71). Although its mechanism of redox regulation is rather complex, NADP-MDH is the best understood of the light-activated enzymes of chloroplasts.…”
Section: Nadp-dependent Malate Dehydrogenasementioning
confidence: 99%
“…They suggested that two disulphide bonds were reduced in vitro during the activation of the maize enzyme compared with 1 disulphide with the pea enzyme. Ferte et al (1986) reported similar but not identical amino acid composition between the maize and pea enzyme; however they reported that both enzymes had three cysteine per monomer.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies report higher subunit mol wts of between 42,000 and 43,000 (7,10). Some workers find the native forms of both the active (reduced, light activated) and unactivated (oxidized, dark inactivated) forms ofNADP-MDH (4) to be apparent dimers with a mol wt of about 88,000 (5,10). However, other studies using gel filtration procedures have indicated higher mol wts (2) and that the activated enzyme has a higher apparent mol wt than the unactivated enzyme (1 1).…”
Section: Methodsmentioning
confidence: 99%